Controller Concept for an Automated Coexistence Management. Issue 10 (2018) - Schulze, Darina; Jumar, Ulrich
Abstract: Several wireless communication systems operating in parallel are typical for industrial applications. These systems have to be coexistent in order to fulfil all their application communication requirements. Ensuring this coexistence is called coexistence management. In this contribution we present a controller concept for an automated coexistence management process. We transform the communication based notation into the control engineering notation for description of the control circuit. Therefore, we introduce a centralised and decentralised control algorithm concept.